Vacuum-assisted impregnation derived α-Bi2O3/TiO2 nanotube arrays with enhanced photoelectrochemical activity - Liu, Y.; Zhao, Q.; Li, Xin Yong; Shi, Y.; Li, T. (Elsevier, 2015)
With the aim of improving the performance of TiO2 nanotube arrays (NTAs), α-Bi2O3 nanoparticles were successfully implanted into the nanotube arrays via a vacuum-assisted impregnation strategy for the first time. Photoelectrochemical characterizations and comparative investigations on the degradation efficiency of 2-Chlorophenol demonstrate the enhanced photo activity of α-Bi2O3/TiO2 nanotube arrays over the pure nanotube arrays. The as-prepared α-Bi2O3/TiO2-NTAs grown on Ti behaved as a recyclable and stable electrode and outperformed pure TiO2-NTAs. The α-Bi2O3 nanoparticles modified TiO2 nanotube arrays could favor the separation and transfer of photoinduced charge carriers, which promote the energy conversion and the generation of reactive radicals upon irradiation. The predominant superoxide radicals were evidenced by electron spin resonance signals.